Optimization of an online shared freight transportation service platform with the use of Conjoint Analysis. Issue 1 (November 2021) - Nalmpantis, Dimitrios; Genitsaris, Evangelos; Amprasi, Vasiliki; Akac, Attila; Anagnostopoulou, Afroditi
Abstract: The purpose of this paper is the optimization of an online shared freight transportation service platform with the use of Conjoint Analysis for the region of Balkan – Mediterranean. A Choice-Based Conjoint analysis was performed amongst the partners of the INTERREG Balkan-Med SCOPE project in order to optimize such a platform which is under development in the frame of the project. The results show that the best possible configuration of the platform should be offered at least in the local language, on a website, in the form of an auction platform, the charging should be done per shipment, and its range should be European / international. Moreover, selecting the right levels for each attribute is of crucial importance for the success of a freight transportation service platform, as the best configuration has a market share that is above 100% of the second-best configuration, according to the market simulation that was performed. Therefore, tools as Conjoint Analysis should be incorporated in the planning and design of such products in order to have the best marketable results for shippers, carriers, and consumers; a product that is customized according to their needs and preferences.